2013
DOI: 10.3109/02699052.2013.793400
|View full text |Cite
|
Sign up to set email alerts
|

False positive diagnosis of malingering due to the use of multiple effort tests

Abstract: False positive rates for effort tests increase significantly as the number of indicators that are administered is increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 37 publications
2
47
1
2
Order By: Relevance
“…He showed that, at an estimated per-test false-positive rate of 10 %, Monte Carlo simulation overestimated error rates. These clinical results run counter to the conclusions arrived at by Berthelson et al (2013) by using the same mathematical simulation procedure that they had used and, therefore, support Larrabee's (e.g., Larrabee, 2012) practice of using the threshold of ≥2 testing validity failures as representative of probable invalid clinical neuropsychological presentation. Odland et al (2015) described that the aim of the Monte Carlo simulation is to provide base rate data and recommendations for interpretation of multiple validity indicators (assuming varying correlations between each PVT), at a range of specificity and sensitivity rates.…”
Section: Reviewmentioning
confidence: 47%
See 2 more Smart Citations
“…He showed that, at an estimated per-test false-positive rate of 10 %, Monte Carlo simulation overestimated error rates. These clinical results run counter to the conclusions arrived at by Berthelson et al (2013) by using the same mathematical simulation procedure that they had used and, therefore, support Larrabee's (e.g., Larrabee, 2012) practice of using the threshold of ≥2 testing validity failures as representative of probable invalid clinical neuropsychological presentation. Odland et al (2015) described that the aim of the Monte Carlo simulation is to provide base rate data and recommendations for interpretation of multiple validity indicators (assuming varying correlations between each PVT), at a range of specificity and sensitivity rates.…”
Section: Reviewmentioning
confidence: 47%
“…Moreover, according to Odland et al (2015), the psychometric characteristics of the validity indicators cited by Larrabee (2014) were fundamentally different from those of Berthelson et al (2013) that he had criticized [and also those in the metaanalysis by Sollman and Berry (2011) that had been involved in the logic used in Berthelson et al (2013)]. Like myself (in Young, 2014a), Odland et al (2015) had argued that, as more PVTs/SVTs are used in evaluations, the probability of increases in Type I error rates increases.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Several approaches have been adopted to determine the number of required deviations. Among them, approaches taking the dependency between test scores into account are to be preferred (Berthelson et al, 2013;Crawford et al, 2007;Muslimovic, Post, Speelman, & Schmand, 2005;Schagen, Muller, Boogerd, Mellenbergh, & van Dam, 2006;Schretlen et al, 2008), as they satisfy the three criteria (e.g., Crawford et al, 2007). That is, they control familywise error at prespecified levels, have adequate sensitivity, and are relatively easy to apply as software exists to determine the number of required deviations (Crawford, 2016).…”
Section: Overall Classification As Impaired or Unimpairedmentioning
confidence: 99%
“…The familywise error issue also is prominent in the normative comparisons context (e.g., Berthelson, Mulchan, Odland, Miller, & Mittenberg, 2013;Bilder, Sugar, & Hellemann, 2014;Brooks, 2010;Crawford et al, 2007;Davis & Millis, 2014;Larrabee, 2008Larrabee, , 2014Loewenstein et al, 2006;Meyers et al, 2014;Naglieri & Paolitto, 2010;Palmer, Boone, Lesser, & Wohl, 1998;Proto et al, 2014;Schretlen et al, 2008). It has been argued that in clinical practice, lack of control over familywise error in normative comparisons may result in overdiagnosis and unnecessary treatment, increasing patient burden and unnecessary costs to the health care system (Binder et al, 2009;Brooks, Iverson, Holdnack, & Feldman, 2008;Gisslén, Price, & Nilsson, 2011;Torti, Focà, Cesana, & Lescure, 2011).…”
mentioning
confidence: 99%